PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 039 AIR TERBIT KECAMATAN TAPUNG - Suci Sekarlangit; Hendri Marhadi; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research was social learning outcomes in fourth grade (IV) students SDN 039 Air Terbit Tapung of subdistrict still low with average value 67,76 (with KKM 70). The purpose of this research was improve social learning outcomes of the fourth grade (IV) srudents SDN 039 Air Terbit Tapung of Subdistrict with the implementation of cooperatif’s STAD type leraning model. This research was classroom action research with two cycles. The subject were students of class IV SDN 039 Air Terbit academic yeras 2015/2016 wich amounted to 21 people consisting 7 women and 14 men. Based on the result a discussion the observation of teacher’s and student activity sheet seen rising each meeting. Teacher’s activity with the implementation of cooperatif’s STAD type learning model at first meeting of first cycle was 62,50% (good), and second meeting was 70,83% (good). At second cycle, teacher’s activity at fisrt meeting was 91,66% (very good) and second meeting was 100% (very good). Students activity with the implementation of cooperatif’s STAD type learning model at first meeting of first cycle was 58,33% (enough), and second meeting was 66,70% (good). At second cycle, students activity at fisrt meeting was 87,58% (very good) and second meeting was 95,80% (very good). Social learning outcomes before implementation of cooperatif’s STAD type learning model average 67,76, after implementation of cooperatif’s STAD type learning model UH I was 79,52 that improve 80,95% and UH II was 87,92 that improve 95,24%. Impementation of cooperatif’s STAD type learning model can improved social learning outcomes of the fouth grade (IV) students SDN 039 Air Terbit Tapung of subdistrict.  Key word: Cooperatife’s STAD type learning model, social studies students         achievement